Juridical Review of People's Business Credit Agreement (KUR) between Customers and PT. Regional Development Banks - Ipmawan Muhammad Iqbal; Moh Indra Bangsawan (Universitas Muhammadiyah Surakarta, 2023)
An agreement is an agreement made between one party and another party in written or verbal form to achieve a certain thing. In borrowing money or credit at a bank or non‐bank institution, there is a written agreement made by the customer with the creditor. In a government program to help the community in terms of capital to build or continue a business, the government issued a people's business credit program that can assist the community in business capital matters. In the people's business credit agreement, the customer who will enter into the agreement must pay attention to the contents or legal constrictions of the agreement and understand how to resolve disputes between the customer and the bank. This study uses a juridical‐empirical research method with interviews with sources involved in people's business credit agreements, so that this research can be useful to the public in order to know the contents of the legal construction of people's business credit agreements and procedures for settling disputes between customers and banks or creditors.